Real dragons - Szymanski, Jennifer (Washington, DC : National Geographic Kids, 2018)
"Find out about dragon-like critters in this new Co-reader from National Geographic Kids. Co-readers provide one page of adult-read-aloud text and one page of kid-read-aloud text on each spread, building toward a collaborative reading experience. Think dragons exist only in fairy tales? Think again! Meet huge komodo dragons, flying lizards, and all sorts of amazing creatures that really are stranger than fiction. Adult and child readers will learn all about fierce and funny REAL dragons together. Co-readers are designed to be read aloud, with one page for the child who is learning to read and the adjacent page for a parent, caregiver, older sibling, buddy, or other more fluent reader. Expert-vetted text along with brilliant photos and a fun approach to reading are a winning formula with kids, parents, and educators"--
OSLIS\Gale Nat Geo eBooks(2/2/23).
Age 2-5.
Pre-school, excluding K.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Animals -- Juvenile literature; Dragons -- Juvenile literature; Lizards -- Juvenile literature; Electronic books- OSLIS